Comparing Genotypic and Phenotypic Variation of Selfed and Outcrossed Progeny of Hemp - Lauren E. Kurtz; Jonathan D. Mahoney; Mark H. Brand; Jessica D. Lubell-Brand (HortScience, 2020)
Feminized hemp seed producers often use selfing to maintain a strain name; however, selfing may lead to inferior plants for cannabidiol (CBD) production. Using three different hemp strains as parents [Candida (CD-1), Dinamed CBD, and Abacus], two outcrosses [Candida (CD-1) × Abacus and Dinamed CBD × Candida (CD-1)] and one self-cross [Candida (CD-1) × Candida (CD-1)] were conducted to produce feminized seed. Progeny from the self-cross were significantly smaller and had less yield than outcrossed progeny. Selfed progeny were variegated and highly variable for total dry weight and floral dry weight. Discriminant analysis of principal components (DAPC) using amplified fragment length polymorphism (AFLP) separated the three progeny populations and showed that outcrossed populations clustered closer to the maternal parent, possibly the result of a maternal effect. Analysis of molecular variance (AMOVA) indicated that most variation (74.5%) was within populations, because the progeny from all three populations are half-siblings of each other. The selfed progeny population had lower expected heterozygosity (He = 0.085) than each of the outcrossed progeny populations (He ≈ 0.10). These results suggest that selfed progeny may demonstrate inbreeding depression resulting from enhanced expression of homozygous recessive traits. It may be beneficial for feminized seed producers to use outcrossing instead of selfing to generate feminized seed for CBD production.